Detectable Impacts of the Past Half‐Degree Global Warming on Summertime Hot Extremes in China. Issue 14 (28th July 2018) - Chen, Yang; Zhai, Panmao; Zhou, Baiquan
Abstract: Avoided risks in a 1.5°C warmer world as opposed to a 2°C one become urgent to be assessed after the Paris Agreement, especially at regional scales. To provide an observable analog, this study quantified detectable impacts of the past 0.5°C global warming on summertime hot extremes in China. The half‐degree global warming has preferentially facilitated the emergence and prevalence of complex hot extremes (sequential hot day‐night), which experienced a twofold‐fourfold increase in their frequency in Southeast China, lower reaches of the Yangtze River, and northern China, along with a doubling to tripling of duration and intensity. The past global warming of 0.5°C further exacerbated the vulnerability of above hot spots by exposing them to drastically augmented (over 300%) excess heat accumulated during the severest complex events. These observation‐based solid evidences imply that a 0.5°C reduction in future global warming does matter for China to avoid excessively escalated risks of complex hot extremes. Plain Language Summary: Since the Paris Agreement was signed, policy‐makers and the general public are eager to know differential risks in a 1.5°C warmer world versus a 2°C one. Does a seemingly small difference of 0.5°C really matter? Along with a yes answer, computer simulation‐based studies also remind us of large uncertainties sourced from flaws of numerical models. Revisiting observational records, we found that the past 0.5°C global warming has already posed detectable impacts on summertime hot extremes in China. Notably, the most damaging type (sequential hot day and night) experienced over threefold increases in the frequency, duration, and intensity, with their sharpest increments recorded in the most populous areas. Increases of these exceptional magnitudes should not have happened without the past 0.5°C global warming. Hence, observational analogs clearly indicate that a 0.5°C difference does matter and will matter for avoiding drastically escalated risks from hot extremes at a regional scale. Key Points: The past half‐degree global warming has already exerted detectable impacts on summertime hot extremes in China The most damaging type of hot extremes exhibited sharpest responsive increases in frequency, duration, and intensity The past half‐degree global warming has significantly altered the dominance among subtypes of hot extremes